From cultural heritage to local economic development: Evidence from consumer purchase intention toward heritage souvenirs in Vietnam - To, Uyen Diep; Thi, Lich Ha; Van, Cuong Le; Trung, Hien Nguyen; Quang, Hung Nguyen (Edelweiss Applied Science and Technology, 2026)
This study aims to examine the impact of four key perception-based variables on consumer purchase intention as a mechanism linking cultural heritage to local economic development through heritage souvenirs in Vietnam. A survey was conducted with a sample of 323 domestic tourists during the Hung Kings Temple Festival in 2025. Using Structural Equation Modeling (SEM), the study evaluates the influence of Perceived Cultural Value (PCV), Perceived Product Price (PPP), Perceived Product Design (PPD), and Perceived Availability (PA) on Purchase Intention (PI). The results reveal that all four constructs have positive and statistically significant effects on PI, with PCV exerting the strongest total impact (β = 0.615), followed by PPP (β = 0.282), PPD (β = 0.268), and PA (β = 0.143). Furthermore, the analysis confirms the mediating role of PPP in the relationship between PCV, PPD, and PI. These findings hold substantial implications for the development of cultural heritage souvenirs. Enhancing the perceived value of heritage through effective product design, appropriate pricing, and improved accessibility can strengthen market acceptance, thereby contributing positively to tourism-driven local economic development. This study provides valuable empirical evidence to support businesses and policymakers in formulating effective strategies aimed at strengthening the cultural heritage souvenir sector.